2022
DOI: 10.1177/25148486221110434
|View full text |Cite
|
Sign up to set email alerts
|

Against settler sustainability: California’s groundwater as a vertical frontier

Abstract: California has been heralded as a beacon of agricultural production and productivity, yet its groundwater crisis is a warning of its impending collapse. In this paper, we argue that policies like California’s Sustainable Groundwater Management Act reinscribe the settler state, even as they aim toward environmental sustainability. Drawing from Indigenous feminist scholarship on water and frontier processes, our methodology traces settler colonialism materially and discursively through the movement of water. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…SGMA designated existing public agencies “with water supply, water management, or land use responsibilities within a groundwater basin” 25 —often agricultural and urban surface water districts—as the GSAs, the implementation vehicles for the reform. This design of SGMA empowered local surface water users who have historically controlled water rights and infrastructure, likely resulting in diminished access (and therefore diminished input) for groundwater-dependent users, such as farmers without district affiliations, tribes, and unincorporated disadvantaged communities 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…SGMA designated existing public agencies “with water supply, water management, or land use responsibilities within a groundwater basin” 25 —often agricultural and urban surface water districts—as the GSAs, the implementation vehicles for the reform. This design of SGMA empowered local surface water users who have historically controlled water rights and infrastructure, likely resulting in diminished access (and therefore diminished input) for groundwater-dependent users, such as farmers without district affiliations, tribes, and unincorporated disadvantaged communities 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In cases where state policy sets polycentric governance in motion, the initial ambiguity of the policy, in this case groundwater sustainability reform, strongly influences its future success and shortcomings. In California, ambiguity within SGMA enabled inconsistent interpretation when it was favorable to local actors or convenient to ignore the sustainability of groundwater resources for Indigenous nations, historically underrepresented groups, and non-agencies 40 .…”
Section: Policy Implications and Recommendationsmentioning
confidence: 99%
“…Contests over hydrosocial territory extend in numerous directions. In California, Underhill et al (2022) argue groundwater has long been mobilized as a vertical frontier to support agricultural production in colonial settlements that undermine Indigenous sovereignty. Correia's (2022) study in the Chaco identified racial assumptions operating through physical sciences to produce oppressive hydrosocial relations of flood and drought on Indigenous territories.…”
Section: Indigenous Hydrosocial Kinshipmentioning
confidence: 99%